Microwave Solvothermal Synthesis of Three-Dimensional Bi(2)MoO(6) Microspheres with Enhanced Photocatalytic Activity - Ma, Shuaishuai (ACS Omega, 2020)
[Image: see text] In this study, three-dimensional (3D) Bi(2)MoO(6) microspheres were successfully fabricated by a facile, rapid, and mild microwave solvothermal strategy for the first time. The resultant 3D Bi(2)MoO(6) microspheres exhibited superior adsorption capacity and photocatalytic efficiency in the degradation of the representative antibiotic ciprofloxacin under visible light, for which the reaction kinetic rate constant is 7.5 times as high as that of the as-synthesized zero-dimensional Bi(2)MoO(6) nanoparticles. The 3D hierarchical porous structure and the high Brunauer–Emmett–Teller surface area providing abundant reactive sites mainly contributed to the enhanced photocatalytic activity. The results highlight the feasibility of 3D Bi(2)MoO(6) microspheres as an efficient visible-light-responsive photocatalyst for antibiotic removal in an aqueous system.